KEPUASAN PENGGUNA APLIKASI SIMPOOL DI KSP BALO’TA: EVALUASI DENGAN FRAMEWORK PIECES - Kartini, Apriani; Maria, Evi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study analyzes user satisfaction with the SIMPOOL application using the PIECES framework. The analysis focuses on employees, evaluating six variables: performance, information and data, economics, control and security, efficiency, and service. The research employs a descriptive quantitative method. The sample consists of employees from Saving and Loan Cooperative Balo’ Toraja (KSP BALO’TA), with 125 respondents. Data were collected and statistically analyzed to assess user satisfaction across each aspect of the PIECES framework. Data were measured using a Likert scale. The results show that the average satisfaction level with the SIMPOOL application is 3.88, with the highest scores in the service, information, and data variables. Other variables, such as performance, control and security, and efficiency, also received positive evaluations, although some areas still need improvement. These findings reinforce the effectiveness of the PIECES framework in evaluating information systems and provide practical recommendations for KSP BALO’TA to enhance the quality of the SIMPOOL application.